The Influence of Work Flexibility on Job Satisfaction with Work Stress as a Mediating Variable - Irzaqi Maulana Rizal; I Gusti Putu Agung Widya Goca; Ni Putu Putri Ayu Wijayanthi (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study intends to analyze the relationship between flexible work arrangements and job satisfaction, with a particular focus on examining whether work-related stress mediates this relationship in the context of GrabBike drivers operating in Denpasar. Methodology/approach: This study adopts a quantitative design with a correlational orientation, where data were gathered through structured survey instruments. The sample consisted of 100 individuals chosen via purposive selection according to predetermined criteria. Data analysis was carried out using SmartPLS version 3.0 by applying the Partial Least Squares–Structural Equation Modeling (PLS-SEM) procedure. Results/findings: Flexibility in working conditions produces positive and significant outcomes for both satisfaction and stress. Conversely, occupational stress neither shows a significant role in shaping job satisfaction nor acts as a mediator in the relationship with flexibility. Conclutions: Work flexibility directly increases job satisfaction among GrabBike drivers, without requiring mediation by work stress. Although work flexibility raises work stress levels, stress does not influence job satisfaction nor mediate the interrelation. Limitations: The study is limited to GrabBike drivers in Denpasar and uses a quantitative approach, which may not fully capture respondents' subjectiveexperiences. Contribution: Practically, the findings offer insights for online transportation service providers in formulating fair and effective flexible work policies. Theoretically, the study enriches literature on work flexibility, stress, and job satisfaction, particularly among informal workers in Indonesia’s digital economy sector.